2018
DOI: 10.17957/ijab/15.0499
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen and Phosphorus Fertilization on Quality and Germination Potential of Smooth Bromegrass Seed

Abstract: A field experiment was conducted to evaluate the effects of two nitrogen levels (N: 0,100 kg ha-1) and four phosphorus levels (P: 0, 60, 90, 120 kg P2O5 ha-1) on smooth bromegrass (Bromus inermis Leyss.) seed quality by measuring germination, mean germination time (MGT), protein and phosphorus contents, acid phosphoesterase (APT) and antioxidant enzymes activities, hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents and electrical conductivity. Nitrogen application improved seed protein content and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The sensitivity of different species germination to nitrogen addition is various (Davis, 2007). Previous studies found that the N application could delay the seed germination rate of Bromus inermis (Zhu, Wang, Yan, Mao, & Mao, 2018). Therefore, the seed germination responses to N treatments were species-specific, mainly positive or unimodal (Ochoa-Hueso & Manrique, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of different species germination to nitrogen addition is various (Davis, 2007). Previous studies found that the N application could delay the seed germination rate of Bromus inermis (Zhu, Wang, Yan, Mao, & Mao, 2018). Therefore, the seed germination responses to N treatments were species-specific, mainly positive or unimodal (Ochoa-Hueso & Manrique, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These nutrient variations further influence seed morphological traits, represented by seed mass (Wu et al, 2018). Zhang et al (2016) concluded that differences in the content of AN in the soil significantly affected the composition of amino acids in the seed (Mon et al, 2016), further promoting the overall content of soluble proteins (CSP) in the seed (Zhu et al, 2018). Additionally, high levels of nitrogen lead to a decrease in the content of crude fat (CCF) in the seed and an opposite trend in CSP and CCF (Urbaniak et al, 2008;Solis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%